Ultrathin Single Bilayer Separation Membranes Based on Hyperbranched Sulfonated Poly(aryleneoxindole). (16th January 2017) - Joseph, Nithya; Thomas, Joice; Ahmadiannamini, Pejman; Van Gorp, Hans; Bernstein, Roy; De Feyter, Steven; Smet, Mario; Dehaen, Wim; Hoogenboom, Richard; Vankelecom, Ivo F. J.
Abstract : The layer‐by‐layer method is an attractive technique for the fabrication of ultrathin nanostructured polyelectrolyte multilayer membranes (PEMM). A simple two‐step procedure is described here for the preparation of an ultrathin, nanostructured membrane comprising a 5–7 nm thick selective layer, consisting only of one single bilayer of poly(diallyldimethylammoniumchloride) and hyperbranched sulfonated poly(aryleneoxindole). These single bilayered membranes exhibit an outstanding solvent‐resistant nanofiltration performance, which is superior to that of commercial membranes as well as to previously reported multilayer membranes having 10–20 bilayers. A comparative study between hyperbranched polyelectrolyte (HPE) and linear polyelectrolyte supports the role of the specific 3D structure of the hyperbranched polyelectrolyte in these excellent separation properties. The work thus encompasses the use of HPEs as an ideal choice for PEMMs, which opens up a new route to significantly decrease the overall membrane preparation time while realizing excellent filtration properties. Abstract : Reducing the number of bilayers, in combination with increasing flux and retention, is an important objective in the emerging field of layer‐by‐layer membranes. By exploiting the unique features of a properly tuned hyperbranched polyelectrolyte as polyanion, a simple and very efficient two‐step strategy is proposed for the synthesis of polyelectrolyte multilayer membranes with outstanding solvent‐resistant nanofiltration properties.